Front Cover Image, Volume 121, Number 6, May 1, 2020. Issue 6 (12th April 2020) - Balci, Deniz; Kirimker, Elvan Onur; Üstüner, Evren; Yilmaz, Ali Abbas; Azap, Alpay
Abstract : The Front Cover image is based on the Technical Note Stage I‐ Laparoscopy‐Partial‐ALPPS Procedure for Perihilar Cholangiocarcinoma by Deniz Balci, Alpay Azap, Elvan Onur Kirimker et al., https://doi.org/10.1002/jso.25868 .